I Issues and Challenges faced by Artisanal and Small-Scale Miners in the Gemstones Sector of Gilgit-Baltistan (GB), Pakistan: Issues and Challenges faced by Artisanal and Small-Scale Miners in the Gemstones Sector of Gilgit-Baltistan (GB), Pakistan - Bangash, Arshad; Dr. Syed Owais (Journal of Peace, Development and Communication, 2023)
This paper presents the narratives of artisanal and small-scale miners (ASM) from the Gilgit-Baltistan (GB) province of Pakistan. The paper draws on the data from fourteen qualitative (semi-structured) interviews and a stakeholder workshop, which were conducted as part of a larger research project to identify factors inhibiting beneficiation of gemstones in Khyber Pakhtunkhwa and Gilgit-Baltistan. The paper finds that GB is full of gemstone deposits and almost all types of gems are mined in the area during mining season (June to September) every year. But throughout the mining season, miners face various types of challenges, which include transportation issues, technological backwardness, absence of safety equipment, shortage of explosives, health and safety issues, environmental issues, financial issues, lack of training opportunities, and marketing and trade issues.